A simple thermal pain model for the evaluation of analgesic activity in healthy subjects - Khambam, Sunil Kumar Reddy (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: Assessment of the analgesic effect of an agent in an experimental pain model permits a level of control not possible in a clinical pain setting and is an ideal approach for evaluation of analgesic drugs. The aim of the present study was to establish a simple and reliable method of producing experimental pain, which can be used for screening of various analgesic agents. MATERIALS AND METHODS: The standardized method was followed in all cases, by recording thermal pain threshold in seconds in 24 healthy volunteers using hot air source at two different speeds, which is equipped in an acrylic-made chamber adjustable to three different levels. Reproducibility of the test procedure was evaluated by recording the thermal threshold parameter by a single observer on two sessions (interday reproducibility) and second observer on one session (interobserver reproducibility) separately. Validity of model was further tested by evaluating the analgesic effect of tramadol on 12 healthy volunteers. RESULTS: Thermal pain model was found to produce low variability with coefficient of variation (CV) less than 10%. Interobserver and interday reproducibility were very good, as shown by Bland–Altman plot, with most of the values within ± 2SD. There was a significant increase in pain threshold time with use of tramadol as compared to placebo which was statistically significant (P < 0.05). CONCLUSION: The newly developed pain model offers a stable and sensitive method for the early assessment of analgesic activity.